Machine-learning based automatic assessment of communication in interpreting - Wang, Xiaoman; Yuan, Lu (Frontiers in Communication, 2023)
Communication assessment in interpreting has developed into an area with new models and continues to receive growing attention in recent years. The process refers to the assessment of messages composed of both “verbal” and “nonverbal” signals. A few relevant studies revolving around automatic scoring investigated the assessment of fluency based on objective temporal measures, and the correlation between the machine translation metrics and human scores. There is no research exploring machine-learning-based automatic scoring in-depth integrating parameters of delivery and information. What remains fundamentally challenging to demonstrate is which parameters, extracted through an automatic methodology, predict more reliable results. This study presents an original study with the aim to propose and test a machine learning approach to automatically assess the communication in English/Chinese interpreting. It proposes to build predictive models using machine learning algorithms, extracting parameters for delivery, and applying a translation quality estimation model for information assessment to describe the final model. It employs the K-nearest neighbour algorithm and support vector machine for further analysis. It is found that the best machine-learning model built with all features by SVM shows an accuracy of 62.96%, which is better than the KNN model with an accuracy of 55.56%. Automatic assessment of communication is expected to complete multi-tasks within a brief period by taking both holistic and analytical approaches to assess accuracy, fidelity and delivery. The proposed automatic scoring system might facilitate human-machine collaboration in the future. It can generate instant feedback for students by evaluating input renditions or abridge the workload for educators in interpreting education by screening performance for subsequent human scoring.